Rapid and sensitive detection of L‐FABP for prediction and diagnosis of acute kidney injury in critically ill patients by chemiluminescent immunoassay. Issue 11 (15th October 2021) - Sun, Tao; Qu, Shufang; Huang, Tiancha; Ping, Ying; Lin, Qinyan; Cao, Ying; Liu, Weiwei; Wang, Danhua; Kong, Piaoping; Tao, Zhihua
Abstract: Background: Acute kidney injury (AKI) was a common clinical complication among critically ill patients in Intensive Care Unit with high morbidity and mortality. Human liver fatty acid‐binding protein (L‐FABP) as a renal tubular injury biomarker was considered a predictor of AKI; however, high‐throughput and sensitive detection methods were still urgently needed. We constructed a sensitive and rapid detection method for detecting L‐FABP and for exploring the clinical application of L‐FABP as a predictor for AKI. Methods: We developed an automated detection method of chemiluminescent immunoassay to measure L‐FABP and evaluated the analytical performance of the new methodology including analytical selectivity, analytical sensitivity, linear range, the minimum limit of detection (LOD), repeatability, and accuracy. One hundred patients were enrolled in this study to explore the predictive and diagnostic ability for AKI. Results: The chemiluminescent immune‐based L‐FABP assay had outstanding analytical sensitivity including the detection limit of 0.88 ng/ml, and a wide linear range of 2 ng/ml to 160 ng/ml. It also exhibited excellent repeatability with intra‐analysis CVs of 8.73%, 4.72%, and 3.79%, respectively, and the inter‐analysis CVs of 13.47%, 7.28%, and 5.94%, respectively. The recovery rate assay exhibited a good accuracy with three L‐FABP concentration of 99.76%, 102.27%, and 96.92%, respectively. The reference interval of L‐FABP was between 0.88 ng/ml and 5.98 ng/ml. The evaluation of predictive and diagnostic performance showed that higher concentration of L‐FABP indicated higher risk of AKI occurrence and disease progression. Conclusions: The clinical application of rapid and sensitive detection method of L‐FABP based on the newly developed chemiluminescent immunoassay could offer benefits for patients. L‐FABP was a potentially predictive and diagnostic biomarker for AKI. Abstract : Concentrations of L‐FABP in heparin‐anticoagulated plasma were detected using a newly developed methodology of paramagnetic‐particle‐based sandwich chemiluminescent immunoassay. Briefly, acridine ester‐labeled anti‐L‐FABP antibodies(detection antibody), samples which contained L‐FABP and biotin‐labeled anti‐L‐FABP antibodies(capture antibody) were mixed in microfuge tubes. After a certain incubation time, mixtures were incubated for another 10 min with adding the liquid containing avidin‐coated paramagnetic particles. After incubation, an external magnetic field was used for removing uncombined paramagnetic particles. Then, adding H2 O2 (trigger solution) into the mixtures for chemiluminescent signal excitation. Samples were analyzed by automated chemiluminescent apparatus.